Clinical Relevance of Persistent Off-Track Hill-Sachs Lesion After Arthroscopic Latarjet Procedure. Issue 8 (July 2021) - Calvo, Claudio; Calvo, Javier; Rojas, Daniel; Valencia, María; Calvo, Emilio
Background: The Latarjet procedure is often used to address off-track Hill-Sachs lesions (OFF-HS) in shoulders with anterior instability. There are concerns as to whether the Latarjet procedure is able to convert all OFF-HS into on-track Hill-Sachs lesions (ON-HS) and whether this limitation could explain the cases of recurrent postoperative instability. Hypothesis: Latarjet surgery converts many preoperative OFF-HS lesions, but not all of them, and there is a difference in the failure rate between shoulders with converted lesions and those with persistent OFF-HS lesions. Study Design: Case series; Level of evidence, 4. Methods: Patients with anterior shoulder instability and an OFF-HS lesion treated with an arthroscopic classic Latarjet procedure between January 2010 and September 2017 were retrospectively evaluated. Patients with moderate or severe shoulder arthrosis, rotator cuff tears, or age older than 50 years were excluded. Glenoid track (GT), HS, HS interval (HSI), and the difference between HSI and GT (ΔHSI-GT) were measured preoperatively. A postoperative computed tomography scan and a clinical evaluation, including the Rowe and Western Ontario Shoulder Instability scores, were performed at a minimum 1- and 2-year follow-up, respectively. Postoperatively, 2 groups of patients were obtained: (1) patients with postoperative persistent OFF-HS; (2) patients with postoperative ON-HS. Clinical and imaging data were compared between the 2 groups. Results: A total of 51 patients (n = 51 shoulders), with a mean age of 29.8 ± 8.4 years (range, 15-50 years), met the inclusion criteria. Six shoulders (11.8%) still showed OFF-HS lesions despite Latarjet surgery. There were no postoperative dislocations, but 3 patients reported subluxations. The subluxation rate was significantly higher in the postoperative persistent OFF-HS group (2 [33%] vs 1 [2.2%]; P = .033). There was a wider preoperative HSI (29.8 ± 2.4 mm vs 22.9 ± 3.5 mm; P < .001) and a larger preoperative ΔHSI-GT (12.2 ± 3.8 mm vs 4.82 ± 3.2 mm; P < .001) in the persistent OFF-HS group. A receiver operating characteristic curve was performed based on preoperative ΔHSI-GT values. A preoperative ΔHSI-GT value ≥7.45 mm predicted a persistent OFF-HS after Latarjet surgery (sensitivity, 100%; specificity, 87%; positive predictive value, 50%; and negative predictive value, 100%). Conclusion: Latarjet surgery converted many preoperative OFF-HS lesions into ON-HS lesions, but not all of them. Six patients (11.8%) retained an OFF-HS and had a statistically significantly higher failure rate after Latarjet surgery compared with those with postoperative ON-HS lesions. Because there were few postoperative OFF-HS lesions and few recurrences, findings are statistically fragile and should be confirmed with larger series.